Cytopathological study of salivary gland lesions by fine needle aspiration cytology - Desai, Priyanka; Gamit, Bhavna; Shahu, Neha S.; Dholiya, Bhavika (International Journal of Research in Medical Sciences, 2019)
Background: Fine needle aspiration cytology is an inexpensive, minimally invasive, outpatient diagnostic procedure. FNA of salivary gland is easier to perform as the site is superficial and repeat FNAC can be perform. As compared to biopsy methods, FNA is a very smooth, cheaper, outpatient procedure helping clinician to save his time for earlier diagnosis and treatment. Though anatomical structure of the gland is very simple, it is subjected to a diverse and heterogenous range of tumors. Methods: The present study on “Cytomorphological features of salivary gland lesion by FNAC” was carried out on department of pathology from June 2015 to June 2017. 65 patients with salivary gland lesions who were sent to pathology department for FNAC were aspirated and correlated histopathologically. Results: Benign salivary gland lesions contribute to majority of cases (54%). Pleomorphic Adenoma was the most common benign salivary gland lesions and Mucoepidermoid Carcinoma was most common malignant lesion. Parotid gland was the most commonly involved in benign tumors and submandibular gland was commonly involved by malignant tumors. Commonly affected age group by benign salivary gland lesion was 31-40 years and those with malignant salivary gland lesion was 41-50 years. Conclusions: FNA cytology provides useful information for the management of salivary gland lesions and prevents unnecessary surgery in cases of nonneoplastic lesions and identification of malignancy helps the surgeon in deciding type and extent of surgery.